2012
DOI: 10.1371/journal.pone.0029076
|View full text |Cite|
|
Sign up to set email alerts
|

NMR Studies on Structure and Dynamics of the Monomeric Derivative of BS-RNase: New Insights for 3D Domain Swapping

Abstract: Three-dimensional domain swapping is a common phenomenon in pancreatic-like ribonucleases. In the aggregated state, these proteins acquire new biological functions, including selective cytotoxicity against tumour cells. RNase A is able to dislocate both N- and C-termini, but usually this process requires denaturing conditions. In contrast, bovine seminal ribonuclease (BS-RNase), which is a homo-dimeric protein sharing 80% of sequence identity with RNase A, occurs natively as a mixture of swapped and unswapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Nevertheless, motions for loop 4, Lys31 (Lys41) and His97 (His119), and conformational changes in the V 1 and V 2 domains, were also recently shown by crystallography to reflect those observed in structurally homologous RNases . Similar conclusions were drawn for monomeric forms of BS‐RNase, which appear to show analogous loop 4 flexibility and allosteric motions neighboring the distant loop 1 (residues 16–22) .…”
Section: Conserved Functional Motions Among Structural Homologssupporting
confidence: 55%
See 1 more Smart Citation
“…Nevertheless, motions for loop 4, Lys31 (Lys41) and His97 (His119), and conformational changes in the V 1 and V 2 domains, were also recently shown by crystallography to reflect those observed in structurally homologous RNases . Similar conclusions were drawn for monomeric forms of BS‐RNase, which appear to show analogous loop 4 flexibility and allosteric motions neighboring the distant loop 1 (residues 16–22) .…”
Section: Conserved Functional Motions Among Structural Homologssupporting
confidence: 55%
“…However, only a restricted set have been subjected to dynamic investigation, considerably restricting flexibility comparisons between evolutionarily diverse enzymes with this structural fold. Although this is not an entirely comprehensive list, experimental and/or theoretical dynamic studies have been performed on free, ligand‐bound, wild‐type and/or mutant forms of human and rat RNase 1 , human eosinophil‐derived neurotoxin (EDN, or RNase 2) , human ECP (or RNase 3) , human RNase 4 , bovine and human angiogenin (hANG, RNase 5) , the northern leopard frog ranpirnase (Onconase) , and monomeric derivatives of bovine seminal RNase (BS‐RNase) . The details of some of these dynamic studies will now be briefly described and compared with the local and global motional behavior of RNase A.…”
Section: Conserved Functional Motions Among Structural Homologsmentioning
confidence: 99%
“…This is likely linked to the sampling of a larger range of conformations, including precursors to unfolding. In order to extract k o and protection factors from the exchange rates, we first evaluated the effect of the pH on k ex, to assess the mechanism by which exchange occurs in the conditions employed for the kinetic measurements . It has been shown that under unimolecular exchange regime (EX1) there is no pH dependence of k ex whereas, in the bimolecular exchange limit (EX2), k ex will be proportional to pH .…”
Section: Resultsmentioning
confidence: 99%
“…Spectral overlapping precluded the possibility of an unambiguous assignment of the other two cysteine pairs. Once a fully active recombinant sample is available a standard heteronuclear NMR study will be possible to evaluate in more detail the structural and dynamical features of the protein in solution, and to provide a more comprehensive mapping of the protein surface exposure, to highlight the potential epitopes eliciting the allergenic properties.…”
Section: Discussionmentioning
confidence: 99%